Characterization of carbapenem resistance mechanisms and integrons inPseudomonas aeruginosastrains from blood samples in a French hospital. Issue 4 (April 2016) - Rojo‐Bezares, Beatriz; Cavalié, Laurent; Dubois, Damien; Oswald, Eric; Torres, Carmen; Sáenz, Yolanda
Abstract : N/A: Metallo‐β‐lactamases (MBLs), porin OprD, integrons, virulence factors and the clonal relationships were characterized in imipenem‐resistant Pseudomonas aeruginosa (IRPA) isolates. Fifty‐six IRPA strains were recovered from blood samples of different patients at a Toulouse teaching hospital from 2011 to 2013. Susceptibility testing of 14 antibiotics was performed by the disc diffusion method. Detection and characterization of MBLs, the oprD gene and integrons were studied by PCR and sequencing. Thirteen genes involved in the virulence of P. aeruginosa were analysed. Molecular typing of IRPA strains was performed by PFGE and multilocus sequence typing. In this study, 61% of the IRPA isolates showed a multi‐resistance phenotype. The MBL phenotype, detected in three isolates (5.4 %), was linked to the bla VIM‐2 gene. The oprD gene was amplified in 55 (98.2 %) IRPA strains, and variations were observed in 54 of them. Insertion sequences (IS) truncating oprD were detected in eight IRPA strains, with the novel IS Pa56 identified in two strains. Class 1 integrons were detected in 24 (42.9 %) IRPA strains. The bla VIM‐2 gene was found inside the class 1 integron arrangements. The new integrons In1054 ( intI1‐aacA56‐qacEΔ1‐sul1 ) and In1160 ( intI1‐aacA4‐aacC1d‐ISKpn4‐gcuE‐qacEΔ1‐sul1 ) have been described for the first time, to the best of our knowledge, in this study. A high clonal diversity was found in our strains. Among the variety of sequence types (STs) found, ST175, ST233, ST235, ST244 and ST654 were noteworthy as epidemic clones. In conclusion, 5.4% of IRPA strains showed an MBL phenotype linked to the bla VIM‐2 gene. The identified oprD high polymorphism could be implicated in the variable resistance to carbapenems in IRPA strains. The dissemination of high‐risk clones is a cause of concern.